THE POSITION OF MULIH DAHA WOMEN IN INSTRUCTION AFTER DIVORCE IN PENARUNGAN VILLAGE, BADUNG, BALI - Putu Emma Viryasari; I Nyoman Sujana; Putu Ayu Sriasih Wesna (Warmadewa Press, 2021)
The Balinese customary law community recognizes kepurusa system; the status of boys is steady, while the status of girls changes, because women after marriage follow their husbands. On that basis, daughters in kepurusa system are never traced or taken into account in inheritance. The purpose of this study is to examine the legal status and the legal position of mulih daha woman in Penarungan Village, Mengwi, Badung, Bali. The method used in this study is an empirical method. Furthermore, this study was carried out by means of field studies, namely by conducting field observations and interviews with respondents and informants. Based on the analysis, the results of this study showed that the legal status of mulih daha woman is received through a procedure with acceptance by the family on a scale and a niskala ceremony is carried out, namely arranging piuning or notification to the ancestral gods that with a divorce from her husband, her daughter has returned to her parents and ask to be accepted back as a damuh or part of her parents' ancestral family so that she can be held accountable again one day when the woman experiences something related to banjar. The legal position of mulih daha women in inheritance is related to the kinship system adopted by the Hindu community in Bali, namely the patrilineal system (fatherhood) where only boys have the right to inherit while girls have no right to inherit but girls can only enjoy the property.